Pengaruh bising lalu lintas terhadap penurunan fungsi pendengaran pada juru parkir di kota Denpasar - Ni Ketut Susilawati; Wayan Sudana; Eka Putra Setiawan (Oto Rhino Laryngologica Indonesiana, 2010)
Background: Noise pollution or noise is an unwanted sound which is disturbing to human beings.However small or soft the sound, if it is undesirable it is considered as noise. Noise induced hearingloss is a sensorineural hearing loss that is commonly encountered second to presbycusis. Purpose: Toknow the effect of traffic noise exposure on hearing impairment to the employees of the Parking DistrictCompany of the Denpasar city and to improve diagnostic detection on hearing impairment caused bynoise. Method: A cross sectional study was conducted at the Parking District Company office. Thepopulations of this study were the employees of the Parking District Company. Samples of this study were the employees who were exposed to traffic noise and control samples were an employee who was unexposed. Samples were selected by simple random sampling. Results: From 40 parking attendants,27 persons (67.5%) aged above 35 years old. The parking attendants who had been working for ten to fifteen years were 36 persons (90%) and no history using ear protection when working. Seven persons(17.5%) had referred DPOAE upon examination with increase hearing threshold on audiogram result.In this study the parking attendants who had hearing deficit induced by noise were 7 persons (17.5%)and only one person (2.5%) in control group. There was a statistically significant effect of traffic noiseto hearing function deficit (p<0.05). Conclusion: Traffic noise has effect in hearing function deficit onthe parking attendants.ORLI Vol. 40 No. 2 Tahun 2010Key words: NIHL, parking attendant, audiometry, DPOAE.